Kesantunan Bahasa dalam Studi Linguistik Pragmatik - Akhmad Saifudin (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2020)
The major aim of this paper is to provide a theoretical view of politeness in a pragmatic perspective. The study was conducted through literature studies on leading theories in language politeness studies, such as Brown and Levinson, Leech, and Ide as well as from observations of the current use of politeness phenomenon, namely interactions in cyberspace. The theoretical view of politeness is given as a result of observations about the reality of using politeness and the synthesis of existing theories.